Applied aquaculture biofloc technology - Felix, S.; Menaga, M. (Boca Raton CRC Press, 2022)
The intent of this book is to provide a detailed and specific set of guidelines for both aquapreneurs and researchers related to the application of Biofloc Technology in aquaculture. This book discusses key issues related to both adoption and practices for aquaculture businesses, how to monitor and assess quality and quantity of biofloc, and how to manage the microbial composition and sludge reduction risk in the fish and shrimp culture. The book works through the specific application of disease management and feed management tools for aquaculture from the perspective of this technology. Particular attention is paid on comparing the prototypes of floc development and evaluation on its efficacy in aquaculture. Note: T & F does not sell or distribute the hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka.
Keywords: Aquacultural biotechnology; Aquaculture; Biotechnologie aquacole